Response Cost: How has it been de ned and studied? - Soares, Paulo Guerra; Costa, Carlos Eduardo; Aló, Raquel Moreira; Luiz, André; Cunha, Talita Regina de Lima (Perspectivas em Análise do Comportamento, 2017)
Three procedures are commonly described as “response cost” in the Experimental Analysis of Behavior. They involve (a) increasing the physical effort necessary to emit the operant response; (b) increasing the requirement for reinforcement (commonly by increasing the reinforcement schedule ratio); or (c) conditional reinforcer loss (such as points or tokens) contingent on the operant response. The goal of this paper was to analyze some of the experimental research that used procedures that exemplify these three definitions of response cost, discussing their differences, similarities and implications for Behavior Analysis. Despite some similarities of the behavioral effects of these three types of procedures, some distinct characteristics could be observed, both in the experimental design and in the behavioral effects observed. Caution is recommended in describing as “response cost” the effects obtained using these three types of experimental design, because sufficient empirical evidence has not been found to indicate that these procedures produce functionally equivalent behavioral effects.